1940
DOI: 10.1111/j.1469-185x.1940.tb00759.x
|View full text |Cite
|
Sign up to set email alerts
|

Les Pigments Des Invertébrés: (À l'EXCEPTION Des Pigments Respiratoires)

Abstract: RéSumé 1. Caroténoïdes. Ces pigments sont beaucoup moins stables qu'on ne le croyait il y a quelques années. Ils s'isomérisent spontanément, s'oxydent en milieu alcalin et se dkcomposent en milieu acide. Ils se trouvent surtout dans les glandes sexuelles et les œufs des Invertébrés et y jouent peut‐être un rôle biologique important. 2. Quinones. Les pigments d'oursins isolés récemment (échinochrome, spino‐chrome et autres) sont des oxy‐naphtoquinones. L'échinochrome, sécrété par les œufs dArbaciu, active les m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
1
3

Year Published

1954
1954
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 115 publications
2
20
1
3
Order By: Relevance
“…). Even though the nature of the green substances has not yet been disclosed, they most likely result from haem breakdown (Lederer, ; Kennedy, ; Rodrigo et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…). Even though the nature of the green substances has not yet been disclosed, they most likely result from haem breakdown (Lederer, ; Kennedy, ; Rodrigo et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Even though the worm's bright green colour is unlikely to act as camouflage, these uncanny green pigments may offer protection against UV light, similarly to melanins (see Riaux-Gobin et al 2000). Even though the nature of the green substances has not yet been disclosed, they most likely result from haem breakdown (Lederer, 1939;Kennedy, 1975;Rodrigo et al 2015). Another possible function of these pigments can be aposematism, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Water-soluble pigments obtained from pterinosomes consist of the pteridines shown in Fig. 3: Two orange and orange-fluorescing, one red and red-fluorescing, and one yellow and yellowfluorescing substances, found in abundance, were identified, respectively, as drosopterin, isodrosopterin, neodrosopterin (hence drosopterin group references 25,26), and sepiapterin (27); two blue, one green, and one violet-fluore, scing, found in large quantity, proved to be biopterin, Ranachrome 3 (presumably, 2-amino-4-hydroxy-6hydroxymethylpteridine) (28), xanthopterin, and isoxanthopterin; one blue and one green-fluorescing, found in smaller amounts, were identified as 2-amino-4-hydroxy-6-carboxypteridine and, presumably, dihydroxanthopterin (24). Besides these substances, three unidentified fluorescent substances were detected: one, found in large quantity, was extremely unstable and easily decomposed to 2-amino-4-hydroxy-6-carboxypteridine, while the others were unknown with respect to chemical structure.…”
Section: Pteridines In Pterinosomesmentioning
confidence: 99%
“…Drosopterin and its enantiomer, isodrosopterin, consist of a pentacyclic ring system containing a 5,6,7,8-tetrahydropterin (ϭ2-amino-5,6,7,8-tetrahydropteridin-4(1H)-one), a 2-amino-3,7,8,9-tetrahydro-4H-pyrimido- [4,5-b] [1,4]diazepin-4-one, and a pyrrole ring (Scheme 1). Based on 1 H NMR and UV/visible spectral analyses, the structure of aurodrosopterin was elucidated in 1993 by Yim et al (5), who found that it is the same as that of drosopterin except that it has one less amino group in the pteridine portion. The presence or absence of an amino group in the pteridine moiety is the key characteristic that distinguishes drosopterin from aurodrosopterin (Scheme 1).…”
mentioning
confidence: 99%